2010
DOI: 10.1111/j.1468-0343.2009.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Political Selection of Firms Into Privatization Programs. Evidence From Romanian Comprehensive Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Gupta et al (2008), in a recent analysis of government priorities and firm sequencing in the Czech mass privatization program, report "strong evidence that the Czech government privatized first firms that were more profitable" (204). Szentpéteri and Telegdy (2010) report similar results in a study of Romanian mass privatization, though they note that an overarching objective of the government in selecting firms was employment preservation, outweighing even potential efficiency gains from privatization. To our knowledge, no existing research or data have suggested that the firms with the least potential were selectively privatized under mass privatization programs.…”
Section: Medvedev 2000; Ganev 2007supporting
confidence: 54%
“…Gupta et al (2008), in a recent analysis of government priorities and firm sequencing in the Czech mass privatization program, report "strong evidence that the Czech government privatized first firms that were more profitable" (204). Szentpéteri and Telegdy (2010) report similar results in a study of Romanian mass privatization, though they note that an overarching objective of the government in selecting firms was employment preservation, outweighing even potential efficiency gains from privatization. To our knowledge, no existing research or data have suggested that the firms with the least potential were selectively privatized under mass privatization programs.…”
Section: Medvedev 2000; Ganev 2007supporting
confidence: 54%
“…Wages have a negative effect on privatization in India and China (Dinc and Gupta, 2011;Liu et al, 2007) while we find that firms with low wages are more likely to remain in state ownership. Finally, Szentpéteri and Telegdy (2010) study Romania by taking advantage of the information on actual privatizations and simulating the possible effects on employment, efficiency and wages, and find similar results to those presented in this article.…”
Section: Empirical Setting and Resultssupporting
confidence: 75%
“…(2007) in China, and Dinc and Gupta (2011) in India. Szentpéteri and Telegdy (2010) study the same question in Romania by estimating the effect of privatization from real data and constructing a counterfactual effect of non‐privatizable firms. De Fraja and Roberts (2009) and Gupta et al.…”
mentioning
confidence: 99%
See 2 more Smart Citations